The internationalization of Malaysian palm oil firms: the role of network relationships / Dato' Anuar Md Nor - Md Nor, Anuar (2016)
There have been many studies conducted on multinationals from large developing Asian countries such as China and India. The multinationals from smaller Asian countries, such as Malaysia, Thailand and Singapore, are also active in investing outside their countries. In particular, the Malaysian multinationals are establishing large-scale oil palm plantations in Indonesia. The Malaysian palm oil-based multinationals, which are defined as POB MNCs, need to invest in Indonesia as they are facing limited suitable lands to plant oil palms domestically. They also have to rely on immigrants labour for their Malaysian oil palm plantations. As a result, the POB MNCs' costs of palm oil production in Malaysia are higher as compared to the costs in Indonesia. The POB MNCs' operations in Indonesia will have a major impact on their long-term business viability as their Malaysian oil palm operations would continue to incur higher production costs. The palm oil industry is important to the Malaysian economy. Thus, the POB MNCs need to be supported by the Malaysian government to develop competitive advantages to operate successfully in Malaysia and Indonesia. The competitive advantages of the POB MNCs have been their superior oil palm plantation management techniques and skilled estate managers, both of which had been accumulated over decades. This study examines the role of network relationships in the Malaysian palm oil industry, and how the network relationships contribute to firm competitive advantages of the POB MNCs. A qualitative research method was used to gather primary data on network relationships by interviewing a sample of informants. They were interviewed from July 2012 to March 2013. Secondary data was also gathered based on archives of industry conferences, annual reports of industry associations and notes made at industry workshops to provide research triangulation. The study shows that network relationships in the palm oil industry were formed as a result of long historical, economic, ownership and personal ties. The members of the network collaborate among themselves to develop solutions to address industry problems, such as access to markets, infestations of pests and diseases on oil palms, and R&D activities. The networks relationships also involve foreign R&D institutions and foreign experts. The study also shows that network relationships had helped in the accumulation of industry best-practices, which are applied in the operations of the POB MNCs in Malaysia and Indonesia. The study has shown that the POB MNCs were able to possess competitive advantages in their Indonesian operations based on the accumulated knowledge of industry best-practices. As a result, the phenomenon of the internationalization of Malaysian palm oil firms in Indonesia was explained in term of their motivation for investing in Indonesia and the possession of competitive advantages over their Indonesian competitors. The study, which is exploratory, contributes to new knowledge on the internationalization of firms from smaller developing countries. There are usual limitations of the study which are associated with the use of a qualitative research method. The results of the study cannot be generalizable to other agro-industry settings. The study has recommended areas that could be addressed in future studies.